EXPLORING THE IMPLEMENTATION OF TEACHING AND LEARNING APPROACHES IN CHILDCARE CENTERS (TASKA): EDUCATORS’ PRACTICES, PARENTS’ ASPIRATIONS, AND EDUCATORS’ CHALLENGES - NUR AINA NADHIRAH DERAMAN; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
The teaching and learning approach is the main pillar in shaping quality education for children's development. This study was conducted to examine the implementation of the teaching and learning approach at TASKA, the aspirations of parents, and the challenges faced by educators during the teaching process. This study uses a semi-structured interview method with three educators at a TASKA in Penang. The findings show that the teaching and learning approach used by educators is based on learning through play, a multisensory approach, and also emotional support to support the holistic development of infants and toddlers. In addition, this study also shows the aspirations of parents towards TASKA and the challenges faced by educators when implementing the teaching and learning process. So this study provides a comprehensive overview of the important role of educators in ensuring the implementation of teaching and learning at TASKA is effective, in addition to the importance of support from parents and employers to ensure the quality of early childhood education is guaranteed.